IMMUNOLOGICAL INDUCTION OF INCREASED VASCULAR PERMEABILITY : II. TWO MECHANISMS OF HISTAMINE RELEASE FROM RABBIT PLATELETS INVOLVING COMPLEMENT - Henson, P. M. (The Rockefeller University Press, 1969)
Two mechanisms have been described whereby rabbit platelets in vitro may be induced to release their contained histamine by the reaction of antigen and antibody. Both processes require the participation of the complement system. In the first, the adherence of platelets to particulate antigens such as zymosan or erythrocytes which have fixed complement through the third component was followed by histamine release. Plasma lacking C6 activity was fully active in this system. In the second mechanism, the reaction of soluble antigen with antibody in the presence of plasma also caused release of histamine from platelets and platelet clumping was observed. The release process, which appeared to follow the adherence of platelets to the immune complex, required the action of C6 and perhaps the later-acting components. No evidence could be obtained that a soluble factor was produced which caused the release. Instead, an inhibitor of the release process was detected after incubation of antigen, antibody, and plasma. Antibody preparations capable of giving complement-dependent PCA reactions in rabbits were also shown to induce the release of histamine from platelets in vitro.